Is Mycoplasma bovis a missing component of the bovine respiratory disease complex in Australia?. Issue 6 (June 2014) - Horwood, PF; Schibrowski, ML; Fowler, EV; Gibson, JS; Barnes, TS; Mahony, TJ
<x xml:space="preserve">Abstract</x> Background Bovine respiratory disease complex (BRDC) is a multi‐factorial disease in which numerous factors, such as animal management, pathogen exposure and environmental conditions, contribute to the development of acute respiratory illness in feedlot cattle. The role of specific pathogens in the development of BRDC has been difficult to define because of the complex nature of the disease and the presence of implicated bacterial pathogens in the upper respiratory tract of healthy animals. Mycoplasma bovis is an important pathogen of cattle and recognised as a major contributor to cases of mastitis, caseonecrotic bronchopneumonia, arthritis and otitis media. To date, the role of M. bovis in the development of BRDC of Australian feeder cattle has not been investigated. Methods In this review, the current literature pertaining to the role of M. bovis in BRDC is evaluated. In addition, preliminary data are presented that identify M. bovis as a potential contributor to BRDC in Australian feedlots, which has not been considered previously. Results and Conclusion The preliminary results demonstrate detection of M. bovis in samples from all feedlots studied. When considered in the context of the reviewed literature, they support the inclusion of M. bovis on the list of pathogens to be considered during investigations into BRDC in Australia.